Observation of the Stacking Faults in In0.53Ga0.47As by Electron Channeling Contrast Imaging. Issue 17 (19th July 2019) - Hsu, Po-Chun (Brent); Han, Han; Simoen, Eddy; Merckling, Clement; Eneman, Geert; Mols, Yves; Collaert, Nadine; Heyns, Marc
Abstract : The observation and interpretation of Frank stacking faults, Shockley stacking faults, Lomer dislocations, and 60° misfit dislocations, which have similar line shapes in the (001) In0.53 Ga0.47 As crystalline surface, are performed with the electron channeling contrast imaging (ECCI) technique. To minimize the backscattered electron (BSE) contrast that resulted from the surface morphology, a relatively flat region is first selected and compared with an atomic force microscopy (AFM) image and then, subsequently, examining ECCI with transmission electron microscopy (TEM)‐like invisibility criteria. By orthogonally choosing the diffraction vector g between (220) and (2‐20), misfit dislocations seem to be always visible but partially faint in the g parallel to the line direction on the surface. With respect to the image contrast, Frank stacking faults and Lomer dislocations are likely to be completely invisible for parallel g . The criteria are further confirmed by cross‐sectional TEM analysis, which shows a preferred homogeneous surface nucleation. Abstract : Two types of stacking faults (SFs) in InGaAs are observed by electron channeling contrast imaging (ECCI). By comparing their shapes and invisibility conditions, Frank SFs, followed by a Lomer–Cottrell lock and glissile SFs with two Shockley partial dislocations, can be distinguished. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) are also performed to validate the results in this study.